Analysis Of Formulation Of Government Internal Supervisory System Policy Using Regulatory Impact Assessment - Suryaman, Ariesca Kamajaya; Umanto (Program Studi Administrasi Negara Universitas Serang Raya, 2025)
The high level of corruption in government makes the effectiveness of supervision from the government's internal control apparatus (APIP) questionable. The current supervisory system that makes APIP less independent is one of the causes of APIP being less than optimal in carrying out its duties and functions. Improving the government's internal supervision system is a discourse that needs to be considered. This study aims to analyze the preparation of government internal supervisory system policies through Regulatory Impact Analysis (RIA). RIA is a useful method in policy formulation to analyze the impact of policies more comprehensively in developing optimal policies. This article uses a qualitative method that aims to understand and explain the process of drafting government internal supervisory system policy in several stages of RIA. The results show that the government has implemented several stages of RIA although there are still shortcomings. The regulation of the government's internal supervisory system is needed to increase the role and independence of APIP. However, the government still needs to increase stakeholder involvement, conduct a cost-benefit analysis, and develop a policy implementation strategy so that the regulations can have an optimal impact.